A cost effective system design and development for remote monitoring of facilities in flatted factories - Manickam Selvakumaran. (2008)
The advancement of technology in most areas largely depends on the development of intelligent devices and its application. These intelligent devices are the programmable logic controllers that are used to perform tasks in different fields. This phenomenon has led to the creation of sophisticated control systems capable of handling huge amount of data processing in increasingly less time as compared with their predecessors.